2022
DOI: 10.1186/s43163-022-00271-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired olfaction post-coronavirus disease 2019: a systematic review of smell recovery predictive factors

Abstract: Background The devastating coronavirus disease (COVID-19) pandemic seemed not yet to cease. Numerous studies regarding its typical sign and symptoms have been done, presenting one of the most promising predictors of the infection: olfactory dysfunction. Although not life-threatening, the symptom could decrease one’s quality of life, especially if persistent throughout their entire life. Among the countless literature regarding loss of smell, only limited studies denote predictors of smell recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In most reviews, Age, gender, and medical comorbidities were predictors of post-COVID-19 olfactory recovery. It is hypothesized that individuals aged<40 years have more tissue injury resistance than older individuals, and the age of >70 years is a predictor of poor long-term recovery from COVID-19-related OD [28], On the other hand, another study found that young adults are at an increased risk of olfactory dysfunction [34]. In contrast to two studies demonstrating a higher recovery rate in women [26, 28], another review concluded that women were more likely to continue the olfactory dysfunction [30].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In most reviews, Age, gender, and medical comorbidities were predictors of post-COVID-19 olfactory recovery. It is hypothesized that individuals aged<40 years have more tissue injury resistance than older individuals, and the age of >70 years is a predictor of poor long-term recovery from COVID-19-related OD [28], On the other hand, another study found that young adults are at an increased risk of olfactory dysfunction [34]. In contrast to two studies demonstrating a higher recovery rate in women [26, 28], another review concluded that women were more likely to continue the olfactory dysfunction [30].…”
Section: Resultsmentioning
confidence: 99%
“…It is hypothesized that individuals aged<40 years have more tissue injury resistance than older individuals, and the age of >70 years is a predictor of poor long-term recovery from COVID-19-related OD [28], On the other hand, another study found that young adults are at an increased risk of olfactory dysfunction [34]. In contrast to two studies demonstrating a higher recovery rate in women [26, 28], another review concluded that women were more likely to continue the olfactory dysfunction [30]. A less severe form of COVID-19 disease in non-hospitalized patients is associated with a greater prevalence of anosmia, and longer symptoms [26, 31, 33].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations